Digital gaps and challenges of legal security - Brahim, Derdiche; Omar, Nessil (The International tax journal, 2025)
The rapid scientific development witnessed by the world has turned it into a small village, leading to many technological transformations that have impacted various communities and groups. These changes have influenced the patterns of economic, social, cultural, and other aspects of life. The spread of modern technologies, social media, digital applications, and others has posed a significant threat to the social fabric and the balance that ensures legal security. Despite the numerous advantages of the virtual environment on minds and their thinking patterns, as well as the scientific and life approaches they adopt, this is accompanied by many negative consequences that have become substantial threats and challenges to society as a whole. Hence, the importance of information security arises, along with how to employ its diverse methods and various applications to confront these threats. The role of information services and its functions as a profession, with its methodologies, models, and scientific approaches, significantly contribute to protecting all segments of society from becoming victims of many different problems and challenges, including threats from the digital environment.